(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective: To investigate how the use of managerial accounting tools reflects in the management and decision-making in a Multiprofessional Clinic in the city of Guarapuava - PR. Method: A questionnaire structured in 3 blocks was applied to employees in the Administrative, Financial and Accounting sectors. Block 1 dealt with managerial accounting tools, block 2 with the importance attributed to managerial accounting tools, in this block, the tools were segregated into operational controls, Financial Statements, costing methods and other managerial artifacts. In block 3, a semi-structured interview was conducted, in which each employee commented on 7 propositions related to their perception of managerial accounting tools and their impact on management and decision-making. Results: The findings indicate that the Accountant and the Controller play an important role in decision-making within the Multiprofessional Clinic. In general, management accounting tools are used to visualize the progress of the business and, on the other hand, contribute to decision-making and business management. It was observed that operational controls are the most used in the Clinic and that not all employees understand all the information contained in accounting reports, considering that they work in the administrative/accounting segment, but their academic training is in another area. Contributions: Evidence that general accounting tools are important in the management of organizations, although in the present research their use is not integral by the collaborators, it emphasizes the importance of such tools as the processes are detailed and understood in an analytical way.